Research Development in Public Universities in Nigeria: Problems and Solutions - Okwelogu Izunna SOMADINA; Victoria Abiodun AYO; Victor Olugbenga AYOKO (Journal of Higher Education and Academic Advancement, 2024)
This paper discussed barriers to research development in Nigerian public universities. Secondary data were used to support the points raised in the article. The secondary data were sourced from print materials and online publications by recognized institutions and individual authors. The paper concluded that Poor funding, lack of modern laboratories, inadequate infrastructure facilities, strike actions, insecurity, brain drain, the poor linkages between researchers and the industrial sector, unattractive working conditions for researchers, strict guidelines for accessing grants and poor mentorship are some of the barriers to research development in public universities in Nigeria. To solve the identified problems, the paper among other things recommended adequate funding of public universities with a special interest in research development in all the public universities in Nigeria.